Solitary Wave Solutions of the Generalized (3+1)-Dimensional Shallow Water-Like Equation by Using Modified Kudryashov Method - Yokuş, Asıf (Adiyaman University, 2021)
In this study, the generalized (3+1)-dimensional Shallow Water-Like (SWL) equation, which is one of the evolution equations, is taken into consideration. With the help of this evolution equation discussed, the modified Kudryashov method, traveling wave solutions are successfully obtained. In these solutions, graphs of solitary waves to be obtained by giving special values to arbitrary parameters are presented. At the same time, the effect of change of velocity parameter on the behavior on the solitary wave is examined in the solution obtained. The breaking of the wave is discussed. In this study, complex operations and graphic presentations are presented with the use of a ready-made package program. © 2021, Adiyaman University. All rights reserved.
Modifiye Kudryashov Metodu Kullanılarak Genelleştirilmiş (3 + 1)-Boyutlu Sığ Su Benzeri Denkleminin Solitary Dalga Çözümleri
Keywords: Generalized (3+1)-dimensional Shallow Water-Like equation; Modified Kudryashov method; Traveling wave solution